The influence of economic factors on police crime recording behavior in the United States between 1960 and 1980 - Bohm, Robert M. (American journal of criminal justice, 1988)
This study examines the influence of certain economic factors (inflation, unemployment, credit, competition, profit and inequality), total social welfare expenditures, and total number of full-time officers, derived from a radical theory of police behavior, on police crime recording behavior in the United States between 1960 and 1980. In contrast to previous research, which has failed to provide a single model that explains over fifty percent of the variance in the dependent variable (Sherman, 1980), this study found three models that explain over fifty percent of the variance in police crime recording behavior.